2007
DOI: 10.1109/titb.2006.879588
|View full text |Cite
|
Sign up to set email alerts
|

Managing Medical Images and Clinical Information: InCor's Experience

Abstract: Patients usually get medical assistance in several clinics and hospitals during their lifetime, archiving vital information in a dispersed way. Clearly, a proper patient care should take into account that information in order to check for incompatibilities, avoid unnecessary exams, and get relevant clinical history. The Heart Institute (InCor) of São Paulo, Brazil, has been committed to the goal of integrating all exams and clinical information within the institution and other hospitals. Since InCor is one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 11 publications
0
13
0
7
Order By: Relevance
“…Analyzing HIT adoption according to geographical areas with high concentrations of patient subpopulations of interest may also be informative� Studies have found that community-level poverty is a significant determinant of access to health services, with those living in low-income neighborhoods less likely to receive needed care� 87 Areas of extreme poverty, for example, have been shown to have significantly higher premature adult mortality rates� 88 Other studies document that people living in communities with greater concentrations of minority residents have less access to health services and receive poorer quality care� 89,90 We were unable to identify any extant studies that assess HIT adoption rates among providers located in communities with high concentrations of poor or minority residents compared to other communities�…”
Section: Hit Adoption Among Medical Group Practices Located In Minorimentioning
confidence: 99%
“…Analyzing HIT adoption according to geographical areas with high concentrations of patient subpopulations of interest may also be informative� Studies have found that community-level poverty is a significant determinant of access to health services, with those living in low-income neighborhoods less likely to receive needed care� 87 Areas of extreme poverty, for example, have been shown to have significantly higher premature adult mortality rates� 88 Other studies document that people living in communities with greater concentrations of minority residents have less access to health services and receive poorer quality care� 89,90 We were unable to identify any extant studies that assess HIT adoption rates among providers located in communities with high concentrations of poor or minority residents compared to other communities�…”
Section: Hit Adoption Among Medical Group Practices Located In Minorimentioning
confidence: 99%
“…Moreover, an EHR is a fundamental part of health information technology and its use is growing quickly. It can be defined as a set of relevant patient data stored in digital format that allows adequate medical assistance delivered to the patient even in different places and scenarios (Furuie, et al, 2007). It can be organized either on a document-based backbone, or on a structured database system.…”
Section: Introductionmentioning
confidence: 99%
“…Some potential advantages of an EHR over a traditional paper-based patient record involve: distributed and simultaneous access, fast information retrieval, better quality, high availability, higher confidence, etc. (Furuie, et al, 2007). In spite of these advantages, there are several barriers to their adoption such as training, costs, complexity and lack of a national standard for interoperability (Gans, et.…”
Section: Introductionmentioning
confidence: 99%
“…A integração entre eles é fundamental para o bom desempenho do fluxo de trabalho e sabe-se que ela tem sido o grande interesse de médicos e do setor hospitalar em geral (FURUIE et al, 2007). Entretanto, pouco esforço foi realizado no sentido de se integrar sistemas CAD com…”
Section: Lista De Figurasunclassified